Analysis the liquidity risk and return of recruitment money indicators on banks - Saleem Hilai, Jinan (Opción, 2019)
The study attempts to shed light on the indicators of liquidity risk as well as indicators of the return of the investment of funds and their impact on Rafidain Bank via application of standard and statistical models that help in the tests offered and reach the results that achieve or reject the hypothesis. In result, the dynamic ability to predict and absorb the banking risks and their ability to absorb them is logically acceptable. In conclusion, guarantee an appropriate investment policy for the economy will force banks to channel their available funds towards investment instead of freezing them as cash